A congested capacitated multi-level fuzzy facility location problem: An efficient drone delivery system. (August 2019) - Shavarani, Seyed Mahdi; Mosallaeipour, Sam; Golabi, Mahmoud; İzbirak, Gökhan
Highlights: Logistics and economics of an aerial delivery system are investigated. Fuzzy variables are utilized to capture the uncertainties of the problem. A congested model is provided to account for the waiting time of the customers. Multi-level facility location model is used to model different levels of the system. Case studies are provided to illustrate the efficiency of the proposed model. Abstract: Online retailers invest an enormous amount of funds in delivering products to customers. In recent years, these delivery costs have increased as a result of changes in fuel costs, which has brought new challenges to retailers in terms of offering competitive prices. Many retailers have begun to utilize a drone-based aerial delivery system as an alternative solution to overcome the problems related to the high transportation costs and traffic jams in large cities. This study provides a mathematical model for minimizing the total costs of the aerial delivery system concerned with refuel stations, warehouses, drone procurement, and transportation. The waiting time of the customers is restricted based on the M/G/K queueing system. The fuel stations and warehouses are the main components of the network. The demand (occurring at the lowest level) is ultimately satisfied via launch stations (the network's highest level). Refuel stations support drones along their long routes between the launch stations and demand points. To account for the different levels of the facilities, a multi-level facility location approach is utilized. Moreover, the nondeterministic nature of the problem is tackled using fuzzy variables. The ultimate mathematical model is a congested fuzzy capacitated multi-level facility location problem that is solved by the possibilistic approach.